Optimization of stocking weight in carp polyculture ponds under drought prone Barind area of Bangladesh - Talukder, Mohammad Golam Sarowar; Mohsin, ABM; Hossain, Md. Akhtar; Khan, Md. Rafiqual Islam (Journal of Fisheries, 2017)
Increased temperature, decreased water level and reduced culture period of the ponds are considered major problems for aquaculture promotion in drought prone Barind area of Bangladesh. In order to address these problems, an experiment was conducted to optimize the stocking weight for carp polyculture ponds in Tanore Upazila of Rajshahi district. Three different stocking weights were tested under three treatments (T1: 25±0.12 g; T2: 50±0.15 g; T3: 100±0.19 g), each with three replications. Fish growing period (July–December), carp species (Catla catla, Hypopthalmichthys molitrix, Aristichthis nobilis, Labeo rohita and Cirrhinus mrigala), stocking density (7,410 individuals/ha), lime and ash treatment, fertilization and feeding were same for all the treatments. Water quality (water temperature, dissolved oxygen, transparency, pH and alkalinity) and fish growth parameters were monitored monthly. Mean values of water quality parameters were found within the suitable range for fish culture. Treatment T3 varied significantly (P<0.05) than that of other treatments for the mean values of final weight, weight gain, specific growth rate, survival rate and yield of fish. Net benefit of carp polyculture was also found the highest in treatment T3. Use of higher stocking weight can be a suitable option for carp polyculture in ponds under drought prone Barind area.